4D Printing of Lead Zirconate Titanate Piezoelectric Composites Transducer Based on Direct Ink Writing - Liu, Kai; Zhang, Qingqing; Zhou, Chenyang; Shi, Yusheng; Sun, Ce; Sun, Huajun; Yin, Changxia; Hu, Jiaming; Zhou, Shuyu; Zhang, Yuzhen; Fu, Yu (Frontiers in Materials, 2021)
Lead zirconate titanate (PZT) piezoelectric composites used in transducer were fabriated via direct ink writing (DIW) combined with furnace firing and resin impregnation. A proper viscoelasticity and high solid loading ceramic/polymer composite pastes were prepared, with a solid state of about 52 vol%. After post-process, the PZT ceramic specimens showed a nanometer-level grain size with a density of 7.63 g/cm3, accounting for 97.8% of the theoretical density. The effect of different printing rod spacing on the electrical properties of composites was evaluated and lucubrated. Finally, an underwater acoustic transducer was assembled by using the PZT Piezoelectric Composites fabricated by the above method. The electrical signal generated by underwater acoustic transducer changed autonomously with the acoustic stimulation, which indicated the application mode of 4D printing in functional devices in future.